2018
DOI: 10.3390/ma11102010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Conductivity Properties of Enhanced Phases in Mg-Zn-Zr System from First Principles

Abstract: In this paper, the mechanical properties and minimum thermal conductivity of ZnZr, Zn2Zr, Zn2Zr3, and MgZn2 are calculated from first principles. The results show that the considered Zn-Zr intermetallic compounds are effective strengthening phases compared to MgZn2 based on the calculated elastic constants and polycrystalline bulk modulus B, shear modulus G, and Young’s modulus E. Meanwhile, the strong Zn-Zr ionic bondings in ZnZr, Zn2Zr, and Zn2Zr3 alloys lead to the characteristics of a higher modulus but lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…From references [33,34] it is known that the studied Mg-1Zn-1Ca alloy presents lower amounts of alloying elements diluted in the matrix than the Mg-3Zn-0.4Ca alloy, favouring the thermal conductivity of the former one. It has been 16 observed that the thermal conductivity of precipitated phases increases with the speed of sound in them, which is high for the MgZn [40]. Also, they are more abundant in the Mg-1Zn-1Ca alloy, favouring the thermal conductivity of this alloy.…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…From references [33,34] it is known that the studied Mg-1Zn-1Ca alloy presents lower amounts of alloying elements diluted in the matrix than the Mg-3Zn-0.4Ca alloy, favouring the thermal conductivity of the former one. It has been 16 observed that the thermal conductivity of precipitated phases increases with the speed of sound in them, which is high for the MgZn [40]. Also, they are more abundant in the Mg-1Zn-1Ca alloy, favouring the thermal conductivity of this alloy.…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…4,5,7,[15][16][17] On the other hand, the detailed atomistic level insight from theoretical studies may provide useful information for synthesizing alloys in experiments with boosted specific properties. 14,[18][19][20][21] Prominent examples can be found in aluminium alloys that play increasingly crucial roles in various industrial products. 5,[8][9][10][11][12][22][23][24][25] One of the main goals of alloying matrices is to obtain the most lightweight and high-strength alloys that can be extensively used in aircraft industries, modern trains and vehicles, and so forth.…”
Section: Introductionmentioning
confidence: 99%